2013
DOI: 10.1038/srep02227
|View full text |Cite
|
Sign up to set email alerts
|

Memory suppression trades prolonged fear and sleep-dependent fear plasticity for the avoidance of current fear

Abstract: Sleep deprivation immediately following an aversive event reduces fear by preventing memory consolidation during homeostatic sleep. This suggests that acute insomnia might act prophylactically against the development of posttraumatic stress disorder (PTSD) even though it is also a possible risk factor for PTSD. We examined total sleep deprivation and memory suppression to evaluate the effects of these interventions on subsequent aversive memory formation and fear conditioning. Active suppression of aversive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Those in the Extreme severity group also reported more severe insomnia symptoms than patients in all the other severity levels. These results correspond with previous FA literature which has demonstrated a relationship between patient‐reported disability, depressive symptoms, and insom‐nia . A number of earlier studies have found a relationship between FA and pain intensity but, after correcting for type I error, pain intensity was not significantly different among the FACS severity groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Those in the Extreme severity group also reported more severe insomnia symptoms than patients in all the other severity levels. These results correspond with previous FA literature which has demonstrated a relationship between patient‐reported disability, depressive symptoms, and insom‐nia . A number of earlier studies have found a relationship between FA and pain intensity but, after correcting for type I error, pain intensity was not significantly different among the FACS severity groups.…”
Section: Discussionsupporting
confidence: 90%
“…Both the CMPD and psychiatric evaluation pain patient samples were assessed for demographic information and completed the FACS. Patients with CMPD also completed a battery of psychosocial PRO measures of pain intensity,perceived disability, depressive symptoms, and insomnia, which have been shown in previous studies to be associated with FA. The pain visual analogue scale (pain VAS) is scored from 0 to 10 and assessed each patient's pain level in response to his or her injury.…”
Section: Methodsmentioning
confidence: 99%
“…They therefore suggested that posttraumatic insomnia might adaptively serve to diminish the generalization of conditioned fear that could follow trauma. However, in a subsequent study (Kuriyama, Honma, Yoshiike, & Kim, 2013), when these same investigators added an active memory suppression procedure (directed forgetting) following encoding on the same task, TSD produced a generalized increase rather than decrease in physiological fear expression, while TSD following directed remembering of the fearful stimuli replicated the previously observed generalized decease in fear expression upon recall testing. These authors attributed this differing effect to interference with hippocampal processing of context and prefrontal regulation of amygdala responses that was produced by the directed forgetting procedure at encoding.…”
Section: Interaction Of Fear Extinction and Sleepmentioning
confidence: 72%
“…It has further been shown that sleep after directed forgetting instructions during the encoding of emotional film clips increased physiological stress responses while watching images from these films during a subsequent re-test, without affecting explicit memory performance (Kuriyama, Honma, Yoshiike, & Kim, 2013). This indicates that emotional processing during sleep differs depending on if participants are instructed to remember or to suppress during encoding.…”
Section: Sleep and Emotional Memorymentioning
confidence: 99%